[OP.4A.08] ANTIDEPRESSANT USE IS RELATED TO LOWER BAROREFLEX SENSITIVITY INDEPENDENTLY OF THE SEVERITY OF DEPRESSIVE SYMPTOMS. THE PARIS PROSPECTIVE STUDY III. (September 2016) - Empana, J.P.; Prugger, C.; Thomas, F.; Perier, M.C.; Zanoli, L.; Guibout, C.; Lemogne, C.; Laurent, S.; Pannier, B.; Parati, G.; Boutouyrie, P.; Jouven, X.
Abstract : Objective: Antidepressant drugs (ATD) are widely used in general medicine in France for treatment of high depressive symptoms and milder depressive manifestations. Although these drugs have marked effects on blood pressure and especially orthostatic hypotension, the respective relationships between high depressive symptoms and ATD with baroreflex sensitivity (BRS) has never been studied on a wide scale. Furthermore, this class of drugs is heterogeneous and subclasses of drugs may have different effect on blood pressure regulation. Design and method: We took advantage of the Paris Prospective Study III (PPS3) study, which includes 10, 154 subjects from the general population, aged 50 to 75. Information on antidepressants use was obtained on a face-to-face interview with the investigator. BRS was investigated by spectral analysis of the spontaneous carotid distension rate and RR intervals using non-invasive high-resolution ultrasound carotid-echotracking. A total score superior or equal to 7 on a 13-item standardized questionnaire defined the presence of high depressive symptoms, the most recent medical prescriptions and/or medical package. The associations between high depressive symptoms, ATD use and low BRS (below the median) was quantified by logistic regression adjusted for age, sex, past history of cardiovascular disease, education, single status, smoking status, hypertension, diabetes, body mass index, resting heart rate, and physical activity. Results: Among the 9213 studied participants aged 50–75 years (38.6% of women), respectively, 5.6% and 5.2% had high-depressive symptoms and were on ATD. High depressive symptoms were not associated with low BRS even in unadjusted analysis (OR = 1.09; 95% CI: 0.91–1.30). Instead, ATD use was related to low BRS in multivariate analysis (OR = 1.27; 95% CI: 1.04–1.54). This association remains after adjusting for and matching on propensity score of receiving ATD. Exploratory analysis suggests a strong association with serotonin and norepinephrine reuptake inhibitors (OR = 1.94; 95% CI: 1.16–3.22). Conclusions: To conclude, antidepressant use but not high depressive symptoms is associated with low BRS. If confirmed, these results may bring novel insights in the mechanisms linking depressive symptoms and/or ATD use with hypertension and cardiovascular disease onset.